AMPLE-CGE model: User guide - Ivory Myka R. Galang (Philippine Institute for Development Studies (PIDS), 2017)
This user guide is written to help prospective users learn how to navigate and run the AMPLE-CGE model. In the beginning, users will learn how to run the finished model and to display results in a software called Generalized Algebraic Modeling System or GAMS. Subsequently, the significance of and other important instructions concerning each part of the model code are explained. The construction and updating of the Philippine social accounting matrix are discussed toward the end. Assuming that users are familiar with computable general equilibrium modelling and with the use of GAMS, they should be able to replicate the results of the AMPLE-CGE model.
Keywords: 330; computable general equilibrium modelling; social accounting matrix